PEMANFAATAN DAUN TEH SEBAGAI BIOSORBEN LOGAM BERAT DALAM AIR LIMBAH (REVIEW) - Irvan Kurnia Wijaya; Yusti Farra Yulia; Kartika Udyani (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
Wastewater contains various types of hazardous chemical compounds that can cause environmental pollution such as heavy metals Zn, Pb, Cu, Cr, Cd, Co, Fe, Mn, Ni, Hg, and As. For this reason, it is necessary to treat waste before it is discharged into the river. Wastewater treatment that can be done by biosorption methods, because it is more efficient and economical. The purpose of this study is to determine the benefit of tea leaves as a biosorbent to absorb heavy metals in wastewater. In this study the biosorption method was used using untreated tea leaves biosorbents, as well as activated and modified chemicals. The results of this study found that untreated tea leaves biosorbent were able to absorb heavy metals Zn, Pb, Cu, and Cr with absorption efficiency of 59,46 – 99,7%, activated and chemically modified tea leaves biosorbents were able to absorb heavy metals Zn, Cd, Co, Pb, Cu, Fe, Mn, Ni, Cr, Hg, and As with absorption efficiency of 68,68-100%. Keywords: Heavy Metals, Biosorbents, Biosorption, Efficiency, and Tea Leaves